Do family values and reproductive health knowledge influence reproductive health-promoting behaviors in married women? A cross-sectional survey - Sun Jeong Yun; Hye Young Kim (Korean Society of Women Health Nursing, 2022)
Purpose Based on the World Health Organization framework on reproductive health, this descriptive correlational study investigated the factors affecting reproductive health-promoting behaviors of married women, with a focus on family values and reproductive health knowledge. Methods A cross-sectional survey was conducted on 170 married women between the ages of 25 and 49 years living in Daegu, Korea. The general and reproductive health characteristics, family values, and reproductive health knowledge of married women were identified, as well as factors affecting reproductive health-promoting behaviors. A questionnaire survey was administered to investigate the impact of various factors on reproductive health-promoting behaviors. Results Positive correlations were shown for health promotion behaviors with family values (r=.78, p<.001) and reproductive health knowledge (r=.55, p<.001). Family values (β=.35, p<.001) and reproductive health knowledge (β=.24, p<.001) were identified as factors influencing reproductive health-promoting behaviors. According to the regression model, the explanatory power of factors affecting reproductive health-promoting behaviors among married women was 51.2%. Conclusion A history of reproductive diseases, family values, and reproductive health knowledge were identified as factors influencing reproductive health-promoting behaviors. These results provide basic data for the development of a reproductive health-promoting program, including a positive approach to reproductive health among married women, and can serve as a basis for further research on intervention strategies.